Simvastatin Inhibits CYR61 Expression in Orbital Fibroblasts in Graves’ Ophthalmopathy through the Regulation of FoxO3a Signaling - Yi-Hsuan Wei; Shu-Lang Liao; Chia-Chun Wang; Sen-Hsu Wang; Wan-Chun Tang; Chang-Hao Yang (Mediators of Inflammation)
Graves’ ophthalmopathy (GO), which is characterized by orbital tissue inflammation, expansion, and fibrosis, is the ocular manifestation in 25% to 50% of patients with Graves’ disease. As the pathology of GO is driven by autoimmune inflammation, many proinflammatory cytokines/chemokines, including TNF-α, IL-1β, IL-6, and CCL20, are crucial in the pathogenesis of GO to activate the orbital fibroblasts. Cysteine-rich protein 61 (CYR61), which is known to regulate cell proliferation, adhesion, and migration, plays a proinflammatory role in the pathogenesis of many inflammatory diseases, such as rheumatoid arthritis. CYR61 was considered a potential biomarker of GO in recent studies. Statins, which are cholesterol-lowering drugs, were found to reduce the risk of GO, probably through their anti-inflammatory and immunomodulatory effects. In this study, we established a link between CYR61 and statins in the pathogenesis and potential treatment for GO. Firstly, our data showed the overexpression of CYR61 in the orbital tissue (n=4) and serum specimens (n=6) obtained from the patients with inactive GO. CYR61 could induce the production of IL-6 and CCL20 in cultured GO orbital fibroblasts. The expression of CYR61 in cultured GO orbital fibroblasts was upregulated via TNF-α stimulation. Secondly, we pretreated cultured GO orbital fibroblasts using simvastatin, a statin, followed by TNF-α stimulation. The data revealed that simvastatin could inhibit TNF-α-induced CYR61 expression by modulating the activity of transcription factor FoxO3a. Our results provided insights into some cellular mechanisms that may explain the possible protective effects of simvastatin against the development of GO.